The separate and combined effects of adiposity and cardiometabolic dysfunction on the risk of recurrent cardiovascular events and mortality in patients with manifest vascular disease - van der Leeuw, J; van der Graaf, Y; Nathoe, H M; de Borst, G J; Kappelle, L J; Visseren, F L J (Heart (British Cardiac Society), 2014)
Objectives A remarkable variation exists in the cardiometabolic consequences of obesity. We evaluated the separate and combined effects of adiposity and cardiometabolic dysfunction on the occurrence of cardiovascular events and mortality in patients with vascular disease. Methods We prospectively followed 5231 patients with a history of clinical cardiovascular disease without diabetes from the Second Manifestations of ARTerial disease (SMART) study. Patients were classified according to body mass index and cardiometabolic function. The presence of cardiometabolic dysfunction was defined as ≥3 of the modified National Cholesterol Education Program (NCEP) metabolic syndrome criteria (waist circumference replaced by elevated C-reactive protein). Cox proportional-hazards analysis was used to estimate HRs for cardiovascular events and mortality. Results The prevalence of cardiometabolic dysfunction was 40% in normal weight, 58% in overweight and 75% in obese patients. During a median follow-up of 6.1 years, 769 patients died and 705 patients experienced a major cardiovascular event. In the absence of cardiometabolic dysfunction, overweight (HR 1.18, 95% CI 0.90 to 1.55) and obese patients (HR 0.93, 95% CI 0.53 to 1.64) were not at increased risk of recurrent major cardiovascular events compared with normal weight patients without cardiometabolic dysfunction. An increased cardiovascular risk was observed in patients with cardiometabolic dysfunction and normal weight (HR 1.58, 95% CI 1.23 to 2.04), overweight (HR 1.35, 95% CI 1.07 to 1.70) and obesity (HR 1.50, 95% CI 1.12 to 2.00) compared with normal weight patients without cardiometabolic dysfunction. A similar pattern was observed for vascular and all-cause mortality. Conclusions In patients with vascular disease, the cardiometabolic consequences of adiposity rather than adiposity per se increase the risk of recurrent cardiovascular events and mortality.